Effect of valproic acid monotherapy on thyroid function on short-term follow-up in children with newly diagnosed epilepsy - Malwade, Sudhir D; Chalipat, Shiji S; Patel, Kinisha; Agarkhedkar, Sharad R; Karambelkar, Geeta R (Indian Journal of Child Health, 2018)
Background: The effect of valproic acid (VPA) monotherapy on thyroid function test is controversial. Objective: The aim of this study is to assess the effect of VPA monotherapy on thyroid function on short-term follow-up in children with newly diagnosed epilepsy. Methods: In this prospective case